Drying kinetics of pumpkin seeds - Cabral de Oliveira, Daniel Emanuel; Guimarães, José Mauro; Gabrielle Souza Bueno, Sarah; da Costa Júnior, José Roberto; Moreira Alves, Estenio; Maciel Costa Silva, Brunno (Comunicata Scientiae, 2021)
The study of drying kinetics is of fundamental importance for mathematical modeling, which has been widely used in the design and analysis of heat and mass transfer processes during drying. The objective of the experiment was to adjust mathematical models to the process drying pumpkin seeds (Cucurbita moschata) genotype Access 53 and cultivating Goianinha under different temperature conditions, determining the mathematical model that can better predict this event, the liquid diffusion and their respective activation energies. The experiment was developed at the Fitotechnics Laboratory of the Federal Institute of Education, Science and Technology of Goiás - Campus Iporá. Eleven mathematical models were used, adjusted by means of non-linear regression analysis by the Gauss-Newton method and for the degree of adjustment, the magnitude of the determination coefficient (R2), the chi-square test (χ2), relative mean error (MRE) and estimated standard deviation (SDE). He found that during the drying of pumpkin seeds the effective diffusion coefficient increases with the increase in temperature in both varieties. The Page model was the one that best described the drying phenomenon of pumpkin seeds genotype Acesso 53 and cv. Goianinha finding activation energy of 39,340 kJ mol-1 for genotype 53 and 43,239 kJ mol-1 for cv. Goianinha.